Solid dispersions with hydrogenated castor oil increase solubility, dissolution rate and intestinal absorption of praziquantel - Chaud, Marco Vinicius; Tamascia, Pollyanna; de Lima, Andreäa Cristina [UNESP]; Paganelli, Maria Ondina; Gremiäo, Maria Palmira Daflon [UNESP]; de Freitas, Osvaldo (FapUNIFESP (SciELO), 2010)
The solubility behavior of drugs remains one of the most challenging aspects in formulation development. Solid Dispersion (SD) has tremendous potential for improving drug solubility. Although praziquantel (PZQ) is the first drug of choice in the treatment of schistosomiasis, its poor solubility has restricted its delivery oral route. In spite of its poor solubility, PZQ is well absorbed in the gastrointestinal tract, but large doses are required to achieve adequate concentration at the target sites. The aim of this study was to improve the solubility and dissolution rate of PZQ and to evaluate its intestinal absorption. SDs were formulated with PEG-60 castor oil hydrogenated (CR-60) using a fusion and evaporation method. Pure PZQ and physical mixtures (PM) and PZQ-CR-60 (2:1; 1:1; 1:2 ratios) were compared as regards their solubility, dissolution and intestinal absorption. The experimental results demonstrated the improvement in the solubility, dissolution rate and intestinal absorption. In addition, the solubility behavior showed pH dependency and that the solubility of PZQ was slower in acidic medium than in neutral and basic mediums. The increase in PZQ solubility of the SD with the CR-60 could be attributed to several factors such as improved wettability, local solubilization, drug particle size reduction and crystalline or, interstitial solid solution reduction.
Keywords: Praziquantel/dissolution rates; Praziquantel/intestinal absorption; Praziquantel/solubility; Solid dispersion